Potensi Industri Fashion Halal Terhadap Perekonomian Islam Di Indonesia - Octaviany, Mega; Sugiharti Binastuti (Taraadin : Jurnal Ekonomi dan Bisnis Islam, 2025)
Indonesia, as the country with the largest Muslim population in the world, has immense potential to develop halal business and has the potential to become a global market for halal products. The fashion industry is one of the most promising halal sectors. The aim of this research is to explore the potential of the halal fashion industry in Indonesia through the applied models and its development strategies. The research method includes literature review, secondary data collection, and qualitative descriptive analysis in the research approach. The research findings indicate that Indonesia has immense potential to develop the halal fashion sector, particularly with the increasing public interest in a lifestyle that values clothing in accordance with Sharia principles. The optimization of halal fashion development can be achieved through design studies based on local wisdom, as well as the establishment of halal industry areas, where public actors and media participate in promoting Islamic lifestyles. It is hoped that this will make Muslims feel more comfortable and familiar with their clothing. With the increasing interest in unique fashion designs, it is expected that the Islamic fashion industry in Indonesia can continue to grow. Keyword : Halal Fashion, Industry, Indonesian Islamic Economy